Predictors influencing expatriates’ job performance in MNCs at Malaysia: host country co-workers’ citizenship behaviour as a moderator / Noor Hafiza Zakariya - Zakariya, Noor Hafiza (2019)
Due to today’s international business environment challenges, international assignments remain a crucial aspect among multinational corporations (MNCs) as their global strategy. Along with the expatriation practices, the issue of expatriates’ job performance remains as a central concern among human resource professional, scholars and practitioners in expatriate research area. Generally, once expatriates could adapt and adjust themselves with host country cultures, norms and values, their job performance also would increase. Several predictors such as family-spouse adjustment perceived organizational support, emotional stability and cultural empathy might influence this relationship. This study also examines the role of host country co-workers’ citizenship behaviour as a moderator on the relationship between expatriate adjustment and expatriate job performance. This study adopts a quantitative approach and based on sample of 139 expatriates residing and working at multinational corporations (MNCs) in Malaysia, the findings reveal that the success of expatriate job performance does not entirely rest on their ability but also from the assistance and courteous behaviour from their host country co-workers. Thus, it was found that the host country co-workers’ citizenship behaviour significantly moderates work adjustment and task performance; and interaction adjustment and contextual performance. Furthermore, the results also show that family-spouse adjustment significantly affects all dimension of expatriate adjustment, and contextual job performance. Further, all dimensions of expatriate adjustment mediates the relationship between family-spouse adjustment and expatriate contextual job performance. On the other hand, perceived organizational support significantly influences general adjustment and work adjustment. While, emotional stability significantly influences interaction adjustment. The present study also found that general adjustment and interaction adjustment have significant relationship with task performance. While, interaction and work adjustment have significant relationship with contextual performance. Therefore, the findings of this study would expand the body of knowledge in expatriate research area especially in international human resource management, expatriate management and cross-cultural management. Furthermore, this study is relevant to human resource development professionals, multinational organizations and expatriating firms in making rational decisions in managing international expatriation to ensure the success of international assignments among their expatriates.